2021
DOI: 10.1093/mnras/stab3393
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical ejecta of neutron star mergers with nucleonic weak processes I: nucleosynthesis

Abstract: We present a coherent study of the impact of neutrino interactions on the r-process element nucleosynthesis and the heating rate produced by the radioactive elements synthesised in the dynamical ejecta of neutron star-neutron star (NS-NS) mergers. We have studied the material ejected from four NS-NS merger systems based on hydrodynamical simulations which handle neutrino effects in an elaborate way by including neutrino equilibration with matter in optically thick regions and re-absorption in optically thin re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
51
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 102 publications
(151 reference statements)
12
51
1
Order By: Relevance
“…Pioneering simulations for binary neutron star mergers with an approximate neutrino treatment in Newtonian gravity (Rosswog et al 1999;Korobkin et al 2012) as well as those in an approximate framework of general-relativistic gravity but without weak interaction (Goriely et al 2011;Bauswein et al 2013) have shown the ejection of very neutron-rich matter (in terms of the electron fraction, Y e < 0.1). However, in this decade, both including the general relativistic gravity, which results in a more violent merger process and hence in higher matter temperature, and taking weak interaction processes into account have significantly altered our understanding on the neutron-richness of the ejecta (Sekiguchi et al 2015;Palenzuela et al 2015;Sekiguchi et al 2016;Foucart et al 2016;Radice et al 2018;Kullmann et al 2022). These works have shown that the dynamical ejecta have a broad distribution of neutron richness (Y e ≈ 0.05-0.4), and as a result, a wide variety of heavy nuclei are now considered to be synthesized via the rapid neutron capture (r-) process (Wanajo et al 2014;Goriely et al 2015;Radice et al 2018;Kullmann et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering simulations for binary neutron star mergers with an approximate neutrino treatment in Newtonian gravity (Rosswog et al 1999;Korobkin et al 2012) as well as those in an approximate framework of general-relativistic gravity but without weak interaction (Goriely et al 2011;Bauswein et al 2013) have shown the ejection of very neutron-rich matter (in terms of the electron fraction, Y e < 0.1). However, in this decade, both including the general relativistic gravity, which results in a more violent merger process and hence in higher matter temperature, and taking weak interaction processes into account have significantly altered our understanding on the neutron-richness of the ejecta (Sekiguchi et al 2015;Palenzuela et al 2015;Sekiguchi et al 2016;Foucart et al 2016;Radice et al 2018;Kullmann et al 2022). These works have shown that the dynamical ejecta have a broad distribution of neutron richness (Y e ≈ 0.05-0.4), and as a result, a wide variety of heavy nuclei are now considered to be synthesized via the rapid neutron capture (r-) process (Wanajo et al 2014;Goriely et al 2015;Radice et al 2018;Kullmann et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In neutron star merger, the heaviest elements are produced mainly in the tidal ejecta component, i.e., in the ejecta that is mostly distributed towards the equatorial plane (e.g., Bauswein et al 2013;Just et al 2015;Sekiguchi et al 2015;Kullmann et al 2022;Just et al 2022). Hence, the kilonova observed in the equatorial direction is likely to show the effect of the presence of lanthanides.…”
Section: Modelmentioning
confidence: 99%
“…Earlier r-process nucleosynthesis studies that adopted either the parametrized BNSM ejecta properties or the outflow trajectories extracted from numerical simulations modeling the post-merger evolution of BNSMs, revealed that a significant amount of actinides with mass fraction X act > ∼ 10 −3 is only produced in ejecta with Y e < ∼ 0.2 [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. This can be qualitatively understood from relating the averaged nuclear mass number at the end of the rprocess ( A f ) to the averaged initial seed nuclear mass number ( A s ) and the abundance ratio of free neutrons to seed nuclei (R n/s ) before the onset of r-process by…”
Section: Theory Requirements and Nuclear Physics Inputsmentioning
confidence: 99%